2019
DOI: 10.1111/aogs.13644
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term cognition and behavior in children born at early term gestation: A systematic review

Abstract: Introduction Recent recommendations characterize deliveries at 37+0 weeks through 38+6 weeks as early term. We aimed to review the literature systematically on long‐term cognition, school performance and behavior in children born early term (37+0 to 38+6 weeks) compared with full term (39+0 to 40+6 weeks). Material and methods The review was performed according to the PRISMA Statement. The final literature search was performed on 31 January 2019. We located studies in PubMed, Embase, CINAHL and Cochrane Librar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 56 publications
2
14
1
1
Order By: Relevance
“…Regarding developmental outcomes of children born early term, previous studies have indicated that they have a slightly increased risk of developmental (e.g., language and cognitive problems) and school functional problems (e.g., lower academic achievement) than their peers born at full term [5,7,8]. However, we did not nd such a difference between early term and full term children in terms of their handwriting performance.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Regarding developmental outcomes of children born early term, previous studies have indicated that they have a slightly increased risk of developmental (e.g., language and cognitive problems) and school functional problems (e.g., lower academic achievement) than their peers born at full term [5,7,8]. However, we did not nd such a difference between early term and full term children in terms of their handwriting performance.…”
Section: Discussioncontrasting
confidence: 93%
“…Therefore, more children born late preterm (23.5%) and early term (14.9%) require early intervention programs as compared to their full term born peers (11.9%) [6]. Those children born late preterm and early term births were found to continue to perform poorer than those born full term, including increased needs for special educational support and scored lower in various academic subjects (reading, math, literacy, and writing) compared to their peers born full term [7][8][9][10]. However, school functioning in these children has not been fully investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In light of the continued global prevalence, and in conjunction with a now critical mass of preterm born adults who survived following the modern neonatal medicine era (post 1970) [2][3][4], research has begun to unravel the long-term consequences of preterm birth. Facilitated by the maturation of preterm birth study cohorts, the literature now provides significant evidence of developmental adversities across the lifespan [5][6][7][8][9]. However, findings are mixed on whether or not individuals born preterm have increased risk of developmental problems or disorders.…”
Section: Rationale (A)mentioning
confidence: 99%
“…There were no instances of BPBP out of 407 cases randomized to induction at 37-38 weeks. Nevertheless, long term cognitive outcomes which peak later, such as school achievement at 16 years of age or attention deficits have to be taken into account with early term delivery [23,24].…”
Section: Management Options Of Lga Pregnanciesmentioning
confidence: 99%